Pengetahuan Ibu Primigravida tentang Preeklamsia di Nusa Tenggara Barat - Novyanti, Baiq Mira; Kristina, Tri Nur; Sudarmiati, Sari (Holistic Nursing and Health Science, 2022)
Introduction: Preeclampsia causes of the most maternal mortality rate in Indonesia. One of factors that lead to high rates of preeclampsia is the lack of knowledge of the mother. Low knowledge can result in mothers not being able to recognize the signs and symptoms of preeclampsia early. The study of maternal knowledge about preeclampsia in Eastern Indonesia is limited, so this study aims to determine the knowledge of primigravida mothers about preeclampsia in Eastern Indonesia.Methods: This research is quantitative descriptive. Respondents in this study were 90 primigravida mothers who did examinations at the Pratama Asy-Syfa clinic and the Ampenan health center in Mataram City. The sampling method used purposive sampling, data collection with questionnaires that had been tested for validity and reliability, and distributed through Whatsapp groups using google form.Results: The knowledge score with the knowledge level classification was good as many as 19 people (31.7%), 33 people (55%), and 8 people lacking (13,3%).Conclusion: Most of the primigravida mothers have sufficient knowledge but there are still those who have less knowledge, so efforts are needed to increase the knowledge of primigravida mothers about preeclampsia. Keywords: Pregnant Women, Knowledge, Attitude.